Environmentally Relevant Concentration of Bisphenol S Shows Slight Effects on SIHUMIx - Schäpe, Stephanie Serena; Krause, Jannike Lea; Masanetz, Rebecca Katharina; Riesbeck, Sarah; Starke, Robert; Rolle-Kampczyk, Ulrike; Eberlein, Christian; Heipieper, Hermann-Josef; Herberth, Gunda; von Bergen, Martin; Jehmlich, Nico (Microorganisms, 2020)
Bisphenol S (BPS) is an industrial chemical used in the process of polymerization of polycarbonate plastics and epoxy resins and thus can be found in various plastic products and thermal papers. The microbiota disrupting effect of BPS on the community structure of the microbiome has already been reported, but little is known on how BPS affects bacterial activity and function. To analyze these effects, we cultivated the simplified human intestinal microbiota (SIHUMIx) in bioreactors at a concentration of 45 µM BPS. By determining biomass, growth of SIHUMIx was followed but no differences during BPS exposure were observed. To validate if the membrane composition was affected, fatty acid methyl esters (FAMEs) profiles were compared. Changes in the individual membrane fatty acid composition could not been described; however, the saturation level of the membranes slightly increased during BPS exposure. By applying targeted metabolomics to quantify short-chain fatty acids (SCFA), it was shown that the activity of SIHUMIx was unaffected. Metaproteomics revealed temporal effect on the community structure and function, showing that BPS has minor effects on the structure or functionality of SIHUMIx.